2004
DOI: 10.1117/12.538481
|View full text |Cite
|
Sign up to set email alerts
|

NIF final optics system: frequency conversion and beam conditioning

Abstract: Installation and commissioning of the first of forty-eight Final Optics Assemblies on the National Ignition Facility was completed this past year. This activity culminated in the delivery of first light to a target. The final optics design is described and selected results from first-article commissioning and performance tests are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(31 citation statements)
references
References 10 publications
0
28
0
Order By: Relevance
“…We were able to provide experimental data demonstrating that high-performance optics can be made and imprinted using MRF using small optics fabricated at LLNL and large-aperture optics made using optimized manufacturing processes. In particular, we have shown that a CPP manufactured using advanced finishing protocols and performed beyond expectation during damage testing by sustaining only two damage sites, one at 12 J/cm 2 and one at 14 J/cm 2 . This result provides a basis for using MRF imprinting as a method of making CPPs that can be placed in either the infrared (1053 nm) and the ultraviolet (351 nm) portions of high-powered laser systems operating at or around 3-nsec pulse width.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We were able to provide experimental data demonstrating that high-performance optics can be made and imprinted using MRF using small optics fabricated at LLNL and large-aperture optics made using optimized manufacturing processes. In particular, we have shown that a CPP manufactured using advanced finishing protocols and performed beyond expectation during damage testing by sustaining only two damage sites, one at 12 J/cm 2 and one at 14 J/cm 2 . This result provides a basis for using MRF imprinting as a method of making CPPs that can be placed in either the infrared (1053 nm) and the ultraviolet (351 nm) portions of high-powered laser systems operating at or around 3-nsec pulse width.…”
Section: Discussionmentioning
confidence: 99%
“…Our development of CPP imprinting technology has, for the most part, focused upon applications where the CPPs are used in the infrared (1053 nm) portion of high-power laser systems and designed for far-field characteristics in the ultraviolet (351 nm) 2,11 . The CPP designs are, however, achromatic and can be used at any wavelength with nearly constant results.…”
Section: Large-aperture Continuous Phase Plates Manufacturementioning
confidence: 99%
See 2 more Smart Citations
“…A major portion of this work centers upon developing and engaging state-of-the-art technology to set the stage for creating nuclear fusion in a laboratory setting. Continuous phase plates (CPPs) form the vital and enabling portion of the optics chain used in these kilojoule-and megajoule-class laser systems because they make it possible to manipulate and control laser beam-shapes, energy distributions, and wavefront profiles 1,2,3,4,5,6,7 . This prescribed beam characteristic control is made possible via manipulation of the incoming wavefront by the CPPs.…”
Section: Large-aperture Cpp Imprintingmentioning
confidence: 99%